Soil health and nutrient dynamics in pasturelands: A decadal study on the effects of alternative vs. prevailing grazing management - Merilynn C. Schantz; Douglas R. Smith; Kabindra Adhikari; Javier M. Osorio Leyton; Douglas R. Tolleson; Douglas (Jeff) J. Goodwin; Kelly R. Thorp; R. Daren Harmel (Agriculture, Ecosystems & Environment, 2026)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Catalyzing progress in the blue economy through joint marine microbiome research across the Atlantic - Alice C. Ortmann; Kelly D. Goodwin; Henk Bolhuis; René Groben; Thulani Makhalanyane; Jeff Bowman; Shawn Robinson; Fabiano Thompson (Frontiers in Marine Science, 2023)
International agreements recognize the importance of cooperative scientific research to conserve and promote sustainable development of a shared Atlantic Ocean. In 2022, the All-Atlantic Ocean Research and Innovation Alliance Declaration was signed. The All-Atlantic Declaration continues and extends relationships forged by the Galway Statement on Atlantic Ocean Cooperation and the Belém Statement on Atlantic Ocean Research and Innovation Cooperation. These efforts are consistent with programs, actions, and aims of the United Nations Decade of Ocean Science for Sustainable Development. In preparation for implementation of the All-Atlantic Declaration, members of the Marine Microbiome Working Group and the Marine Biotechnology Initiative for the Atlantic under the Galway and Belém Statements respectively, joined forces to call for cooperation across the Atlantic to increase marine microbiome and biotechnology research to promote ocean health and a sustainable bioeconomy. This article reviews the goals of the marine microbiome and biotechnology initiatives under the Galway and Belém Statements and outlines an approach to implement those goals under the All-Atlantic Declaration through a Blue Biotech and Marine Microbiome (BBAMM) collaboration.

Genetic features of the marine polychaete Sirsoe methanicola from metagenomic data - Shen Jean Lim; Luke R. Thompson; Kelly D. Goodwin (Frontiers in Marine Science, 2023)
The methane ice worm Sirsoe methanicola is the only marine polychaete species observed to colonize the methane hydrates of the Gulf of Mexico. Methane hydrates are ephemeral features of deep-sea cold seeps, and finding worm-colonized hydrates is rare; thus, little is known about these organisms. Recent metagenomic analysis predicted prokaryotic taxa and pathways from S. methanicola gut contents and worm fragments. Here, we increase the genetic information known about S. methanicola by assembling its nuclear rRNA genes (18S rRNA and 28S rRNA), mitochondrial genome (mitogenome), and other protein-coding genes from metagenomic data. Assembled 18S rRNA and 28S rRNA gene sequences of S. methanicola were near-identical to previously reported S. methanicola sequences. The 17,403-bp mitogenome of S. methanicola is the first mitogenome sequence of the family Hesionidae , consisting of 39.03% G+C content, 13 protein-coding genes, 24 tRNAs (including two split trnM genes), and 2 rRNA genes. Protein-coding genes in the S. methanicola metagenomes assigned to the phylum Annelida were involved in cell adhesion, signaling, ubiquitin system, metabolism, transport, and other processes. From the metagenomes, we also found 42 homologs of the cytochrome P450 (CYP) superfamily putatively involved in polycyclic aromatic hydrocarbon (PAH) metabolism. Our results encourage further studies into the genetic adaptations of S. methanicola to its methane hydrate habitat, especially in the context of deep-sea ecology and nutrient cycling.

Toward Identifying the Critical Ecological Habitat of Larval Fishes: An Environmental DNA Window into Fisheries Management - Erin Satterthwaite; Andrew Allen; Robert Lampe; Zachary Gold; Andrew Thompson; Noelle Bowlin; Rasmus Swalethorp; Kelly Goodwin; Elliott Hazen; Steven Bograd; Stephanie Matthews; Brice Semmens (Oceanography, 2023)
Environmental DNA (eDNA)-based ecological co-occurrence networks can provide a valuable tool for fisheries and conservation management. In the past, it was nearly impossible to explore the microscopic world of larval fishes in one sampling event. Now, eDNA data and ecological co-occurrence network modeling provide windows into ecosystems that support larval fishes and upon which subsequent fisheries rely. Thus, there is great potential for eDNA methods coupled with ecological network analyses to provide a holistic understanding of community composition and species interactions and to develop indicators for fisheries and ecosystem-based management.

Lake Erie field trials to advance autonomous monitoring of cyanobacterial harmful algal blooms - Paul A. Den Uyl; Luke R. Thompson; Reagan M. Errera; James M. Birch; Christina M. Preston; William Ussler; Colleen E. Yancey; Subba Rao Chaganti; Steven A. Ruberg; Gregory J. Doucette; Gregory J. Dick; Christopher A. Scholin; et al. (Frontiers in Marine Science, 2022)
Biomolecular analyses are used to investigate the dynamics of cyanobacterial harmful algal blooms (cyanoHABs), with samples collected during monitoring often analyzed by qPCR and sometimes amplicon and metagenomic sequencing. However, cyanoHAB research and monitoring programs face operational constraints due to the reliance on human resources for sample collections. To address this impediment, a third-generation Environmental Sample Processor (3G ESP) integrated with a long-range autonomous underwater vehicle (LRAUV) was tested during seasonal blooms of Microcystis in western Lake Erie (WLE) in 2018 and 2019. The LRAUV-3G ESP successfully performed flexible, autonomous sampling across a wide range of cyanoHAB conditions, and results indicated equivalency between autonomous and manual methods. No significant differences were found between LRAUV-3G ESP and manual sample collection and handling methods in the 12 parameters tested. Analyzed parameters included concentrations of total cyanobacteria and microcystin toxin gene via qPCR; relative abundances of bacterial amplicon sequence variants (ASVs) from 16S rRNA gene amplicon sequencing; and community diversity measures from both 16S amplicon and metagenomic sequencing. The LRAUV-3G ESP provided additional sampling capacity and revealed differences between field seasons for bacterial taxa and concentrations of total cyanobacteria and microcystin toxin gene. Metagenomic analysis of multiple microcystin toxin genes corroborated the use of the mcyE gene as a proxy for the genomic potential of WLE cyanoHABs to produce microcystin. Overall, this study provides support for the use of autonomous ‘omics capability in WLE to help expand the spatial and temporal coverage of cyanoHAB monitoring operations.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Observing Life in the Sea Using Environmental DNA - Francisco Chavez; Markus Min; Kathleen Pitz; Nathan Truelove; Jacoby Baker; Diana LaScala-Grunewald; Marguerite Blum; Kristine Walz; Charles Nye; Anni Djurhuus; Robert Miller; Kelly Goodwin; et al. (Oceanography, 2021)
The use of environmental DNA (eDNA) for studying the ecology and variability of life in the sea is reviewed here in the context of US interagency Marine Biodiversity Observation Network (MBON) projects. Much of the information in this paper comes from samples collected within US National Marine Sanctuaries. The field of eDNA is relatively new but growing rapidly, and it has the potential to disrupt current paradigms developed on the basis of existing measurement methods. After a general review of the field, we provide specific examples of the type of information that eDNA provides regarding the changing distribution of life in the sea over space (horizontally and vertically) and time. We conclude that eDNA analyses yield results that are similar to those collected using traditional observation methods, are complementary to them, and because of the breadth of information provided, have the potential to improve conservation and management practices. Moreover, through technology development and standardization of methods, eDNA offers a means to scale biological observations globally to a level similar to those currently made for ocean physics and biogeochemistry. This scaling can ultimately result in a far better understanding of global marine biodiversity and contribute to better management and sustainable use of the world ocean. Improved information management systems that track methods and associated metadata, together with international coordination, will be needed to realize a global eDNA observation network.

Trace metal and nitrogen concentrations differentially affect bloom forming cyanobacteria of the genus Dolichospermum - Laura T. Kelly; Marion Champeaud; Veronica Beuzenberg; Eric Goodwin; Piet Verburg; Susanna A. Wood (Aquatic Sciences, 2021)

Finding Crush: Environmental DNA Analysis as a Tool for Tracking the Green Sea Turtle Chelonia mydas in a Marine Estuary - Kirsten J. Harper; Kelly D. Goodwin; Lynsey R. Harper; Erin L. LaCasella; Amy Frey; Peter H. Dutton (Frontiers in Marine Science, 2020)

Global Observational Needs and Resources for Marine Biodiversity - Gabrielle Canonico; Pier Luigi Buttigieg; Enrique Montes; Frank E. Muller-Karger; Carol Stepien; Dawn Wright; Abigail Benson; Brian Helmuth; Mark Costello; Isabel Sousa-Pinto; Hanieh Saeedi; Jan Newton; et al. (Frontiers in Marine Science, 2019)

In situ Autonomous Acquisition and Preservation of Marine Environmental DNA Using an Autonomous Underwater Vehicle - Kevan M. Yamahara; Christina M. Preston; James Birch; Kristine Walz; Roman Marin; Scott Jensen; Douglas Pargett; Brent Roman; William Ussler; Yanwu Zhang; John Ryan; Brett Hobson; et al. (Frontiers in Marine Science, 2019)

DNA Sequencing as a Tool to Monitor Marine Ecological Status - Kelly D. Goodwin; Luke R. Thompson; Bernardo Duarte; Tim Kahlke; Andrew R. Thompson; João C. Marques; Isabel Caçador (Frontiers in Marine Science, 2017)

A reassessment of the soil sink for atmospheric carbon tetrachloride based upon static flux chamber measurements - James D. Happell; Yudania Mendoza; Kelly Goodwin (Journal of Atmospheric Chemistry, 2014)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Production of bromoform and dibromomethane by Giant Kelp: Factors affecting release and comparison to anthropogenic bromine sources - Kelly D. Goodwin; Wheeler J. North; Mary E. Lidstrom (Limnology and Oceanography, 1997)
Macrocystis pyrifera (Giant Kelp), a dominant macroalgal species in southern California, produced 171 ng per g fresh wt (gfwt) per day of CHBr 3 and 48 ng gfwt −1 d −1 of CH 2 Br 2 during laboratory incubations of whole blades. Comparable rates were measured during in situ incubations of intact fronds. Release of CHBr 3 and CH 2 Br 2 by M. pyrifera was affected by light and algal photosynthetic activity, suggesting that environmental factors influencing kelp physiology can affect halomethane release to the atmosphere. Data from H 2 O 2 additions suggest that brominated methane production during darkness is limited by bromide oxidant supply. A bromine budget constructed for a region of southern California indicated that bromine emitted from the use of CH 3 Br as a fumigant (1 × 10 8 g Br yr −1 ) dominates macroalgal sources (3 × 10 6 g Br yr −1 ). Global projections, however, suggest that combined emissions of marine algae (including microalgae) contribute substantial amounts of bromine to the global cycle, perhaps on the same order of magnitude as anthropogenic sources.